Method for improving strength of a molded object and method for manufacturing a reinforced molded object

The method of impregnating molded objects with silica-containing liquids and heat treatments addresses the weaknesses of existing additive manufacturing methods, enhancing strength and stability while reducing gas generation, achieving high bending strength and dimensional stability.

JP7610438B2Active Publication Date: 2025-01-08TAIHEIYO CEMENT CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021042051
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-16
Publication Date
2025-01-08
Estimated Expiration
2041-03-16

AI Technical Summary

Technical Problem

Existing methods for manufacturing molded objects using additive manufacturing face challenges with insufficient early strength development, bending strength, and dimensional stability, particularly in complex shapes, leading to potential cracking and difficulty in achieving mechanical strengths of 10 MPa or more.

Method used

A method involving impregnation with a silica-containing liquid followed by heat treatment at specific temperatures to enhance the strength of molded objects, utilizing silica sol solutions or alkyl silicate solutions, with heat treatments at 800°C or higher, particularly at 1000°C or higher, to improve mechanical properties.

Benefits of technology

The method significantly enhances the strength, dimensional stability, and reduces gas generation during heating, resulting in molded objects with high bending strength and reliable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610438000006
    Figure 0007610438000006
  • Figure 0007610438000007
    Figure 0007610438000007
  • Figure 0007610438000008
    Figure 0007610438000008
Patent Text Reader

Abstract

To provide a method for improving the strength of a molded article and a method for producing a strengthened molded article obtained by improving the strength of a molded article.SOLUTION: A method for improving the strength of a molded article comprises: a step (1) in which a molded article comprising an oxide(s) comprising at least one element selected from the group consisting of Si, Al, Ca, Zr, Ti, Fe, Cr and Mg is subjected to impregnation treatment with at least one or more silica-containing solutions, including a silica sol solution or an alkyl silicate solution; a step (2) in which the molded article treated by the step (1) is subjected to heating treatment at 800°C or more; a step (3) in which the molded article treated by the step (2) is subjected to impregnation treatment with at least one or more silica-containing solutions, including a silica sol solution or an alkyl silicate solution; and a step (4) in which the molded article treated by the step (3) is subjected to heating treatment at 800°C or more, and at least one of the step (2) and the step (4) is the heating treatment at 1,000°C or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for improving the strength of an oxide-containing shaped object, and a method for producing a reinforced shaped object having improved strength. [Background technology]

[0002] Casting is a traditional metal processing method in which molten metal is poured into a mold to produce castings. The hardening molds used in casting can be organic or inorganic, depending on the binder (caking agent) used; of these, the inorganic types are mainly water glass-based and cement-based. However, with cement-based self-hardening molds, depending on the pouring temperature of the metal, the gypsum contained in the binder can thermally decompose, generating gas, causing defects in the casting and impairing its aesthetics and functionality. In addition, the production of this mold requires the creation of a model or wooden pattern as a pre-process, which is time-consuming and costly. Therefore, a method of manufacturing a mold that does not impair the aesthetics of the casting and does not require the above-mentioned pre-process is desired.

[0003] Meanwhile, in recent years, additive manufacturing equipment has been attracting attention as a rapid and precise molding method. For example, a powder lamination molding machine among additive manufacturing equipment is a machine that spreads powder on a flat surface, sprays an aqueous binder onto the powder, and then molds the hardened powder by sequentially stacking it in the vertical direction. The feature of this machine is that it divides the data of a three-dimensional molded body created by 3D CAD or the like into many horizontal planes, and sequentially stacks the shapes of these horizontal planes to manufacture a molded body. If the molded body can be manufactured using the above machine, the above pre-processing will be unnecessary, and the work time and cost can be reduced.

[0004] For example, a technology has been proposed for obtaining a green body by adding an aqueous binder to a material obtained by mixing (kneading) refractory sand such as silica sand, olivine sand, and artificial sand with 15 to 50% of rapid-hardening cement as a hydraulic composition suitable for the binder jetting method (powder laminate molding method), solidifying and laminating the material (see, for example, Patent Document 1). Here, the binder jetting method is a method in which a molding liquid is dripped or sprayed through a nozzle such as an inkjet onto a predetermined area of ​​a powder material placed on a loading platform (pedestal) to solidify it, and the solidified layers are successively laminated to form a desired shape.

[0005] However, molded bodies made from the above materials are prone to chipping due to insufficient early strength development, especially bending strength, and it may be difficult to impart fine shapes, which are a feature of molding technology using additive manufacturing equipment, or to steadily supply products with fine shapes. In addition, when molded bodies of complex shapes such as casting molds are manufactured using the above materials, cracks may occur if dimensional changes such as shrinkage and expansion occur after manufacturing, and if the dimensions of the molded bodies differ, an operation to adjust the dimensions is required. Furthermore, it is desired that the operation of removing the unhardened powder of the hydraulic composition remaining after molding from the molded body (de-powdering) be easy.

[0006] Also, a method has been proposed in which an additive manufacturing object is manufactured using a powder for additive manufacturing that contains a ceramic powder and a binder, and then the additive manufacturing object is fired at a high temperature (see, for example, Patent Document 2). The proposal states that the method produces an additive manufacturing object that has appropriate core strength and other fired physical and chemical properties.

[0007] However, even the above techniques are insufficient to fully satisfy recent requirements for the mechanical strength of additive manufacturing products, such as a bending strength of 10 MPa or more, and there is still room for improvement. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2011-51010 A [Patent Document 2] JP 2015-226935 A Summary of the Invention [Problem to be solved by the invention]

[0009] In light of the above circumstances, an object of the present invention is to provide a method for improving the strength of a shaped object.

[0010] Another object of the present invention is to provide a method for producing a reinforced shaped body having improved strength. [Means for solving the problem]

[0011] As a result of extensive research, the inventors have discovered a new method for improving the strength of a shaped object and a new method for manufacturing a reinforced shaped body, as shown below, and have found that the above-mentioned objects can be achieved by each of the above-mentioned methods, thereby completing the present invention.

[0012] That is, the present invention includes the following aspects.

[0013] Item 1. A step (1) of impregnating a shaped object containing an oxide containing at least one element selected from the group consisting of Si, Al, Ca, Zr, Ti, Fe, Cr, and Mg with at least one silica-containing liquid containing a silica sol solution or an alkyl silicate solution; A step (2) of subjecting the object processed in the step (1) to a heat treatment at 800°C or higher; A step (3) of impregnating the shaped object treated in the step (2) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and The method includes a step (4) of subjecting the shaped object treated in the step (3) to a heat treatment at 800° C. or higher, A method for improving the strength of a shaped object, wherein at least one of the steps (2) or (4) is a heat treatment at 1000°C or higher.

[0014] Item 2. A method for improving strength of a molded object according to item 1, wherein the molded object is manufactured by an additive manufacturing apparatus.

[0015] Item 3. The strength improving method according to Item 1 or 2, wherein the shaped object contains the oxide in an amount of 50 mass % or more based on the entire shaped object.

[0016] Item 4. The strength improving method according to any one of Items 1 to 3, wherein the impregnation treatment in the step (1) is carried out for 5 to 120 seconds.

[0017] Item 5. The strength improving method according to any one of Items 1 to 4, wherein the alkyl silicate in the alkyl silicate solution is an alkyl silicate having a dimer or higher.

[0018] Item 6. The strength improving method according to any one of Items 1 to 4, wherein the alkyl silicate in the alkyl silicate solution is an alkyl silicate having a monomericity of five or more.

[0019] Item 7. The strength improving method according to any one of Items 1 to 6, wherein the heat treatment in the step (2) is performed at 2000° C. or lower.

[0020] Item 8. The strength improving method according to any one of Items 1 to 7, wherein the heat treatment in the step (4) is performed at 2000° C. or lower.

[0021] Section 9.Furthermore, A step (5) of impregnating the shaped object treated in the step (4) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and 9. The strength improving method according to any one of items 1 to 8, further comprising a step (6) of subjecting the shaped object treated in the step (5) to a heat treatment at 800° C. or higher.

[0022] Item 10. The strength improving method according to Item 9, wherein the heat treatment in the step (6) is performed at 2000° C. or lower.

[0023] Item 11. The strength improving method according to any one of Items 1 to 10, wherein the shaped article is used for a casting mold.

[0024] Item 12. A step (1) of impregnating a shaped object containing an oxide containing at least one element selected from the group consisting of Si, Al, Ca, Zr, Ti, Fe, Cr, and Mg with at least one silica-containing liquid containing a silica sol solution or an alkyl silicate solution; A step (2) of subjecting the object processed in the step (1) to a heat treatment at 800°C or higher; A step (3) of impregnating the shaped object treated in the step (2) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and The method includes a step (4) of subjecting the shaped object treated in the step (3) to a heat treatment at 800° C. or higher, A method for producing a reinforced and shaped article, wherein at least one of the steps (2) and (4) is a heat treatment at 1000°C or higher. Effect of the Invention

[0025] By using the method for improving the strength of a shaped object of the present invention, it is possible to improve the strength, dimensional stability, and gas generation during heating of the shaped object.

[0026] Furthermore, by using the method for producing a reinforced shaped article of the present invention, it is possible to easily and reliably obtain a shaped article that has high strength, good dimensional stability, and suppresses gas generation during heating. [Brief description of the drawings]

[0027] [Figure 1] FIG. 1 is a graph showing the evaluation results of a three-point bending strength test in the examples. [Diagram 2] FIG. 2 is a graph showing the evaluation results of the three-point bending strength test in the examples. [Diagram 3] FIG. 3 is a graph showing the evaluation results of the three-point bending strength test in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these embodiments.

[0029] <Sculpture> The shaped article in the present invention contains an oxide containing at least one element selected from the group consisting of Si, Al, Ca, Zr, Ti, Fe, Cr, and Mg.

[0030] The above-mentioned shaped object can be shaped, for example, by using a shaping powder containing particles (hereinafter also referred to as base material particles) containing the above-mentioned oxide. For example, a shaping powder containing base material particles and an adhesive component is prepared, and a shaped object (layered shaped object, etc.) is shaped by using this shaping powder (layered shaped powder, etc.). The above-mentioned base material particles may be particles that undergo a hydration reaction (typically the generation of hydrates or hydroxides) when the particles come into contact with water, or particles that do not undergo a hydration reaction, or even if they do, the hydration reaction is limited to a microscopic range on the surface of the particles, or may be a mixture of these. The above-mentioned base material particles are components that constitute the base material of the shaped object to be shaped. In addition, the oxide containing at least one element selected from the group consisting of Si, Al, Ca, Zr, Ti, Fe, Cr, and Mg contained in the shaped object is not limited to being contained in the above-mentioned base material particles, and the above-mentioned oxide may be added to or mixed with the shaping powder.

[0031] The oxide is not particularly limited, but examples thereof include calcium aluminate (Ca-Al-O), calcium silicate (Ca-Si-O), mullite (Al-Si-O), Al 2 O 3 , ZrO 2 , ZrSiO 4 , SiO 2 , Fe 2 O 3 , FeO, Fe 3 O 4 , chromite (Cr-Fe-Mg-O), olivine (Mg-Fe-Si-O), spinel (MgAl 2 O 4 ), TiO2 These may be used alone or in combination of two or more.

[0032] The material and properties of the base particles are not particularly limited as long as they contain the oxide. For example, the base particles may be inorganic particles such as zirconium silicate, mullite, alumina, blast furnace slag, fly ash, silica fume, hydrophobic fumed silica, sand, rapid hardening cement, cement, silica fine powder, organic particles, and organic-inorganic composite particles.

[0033] The shape of the base particles may be, for example, spherical, elliptical, non-spherical, etc. The average particle size of the base particles is not particularly limited, but may be, for example, 1 μm or more and 200 μm or less. From the viewpoint of moldability, the average particle size of the base particles may be, for example, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. The average particle size of the base particles may be, for example, 200 μm or less, 140 μm or less, 120 μm or less, 100 μm or less, or 80 μm or less.

[0034] In this specification, unless otherwise specified, the term "average particle size" refers to the particle size at an integrated value of 50% in the particle size distribution measured using a particle size distribution measuring device based on a laser scattering / diffraction method, i.e., the 50% volume average particle size (D50 size).

[0035] The content of the base material particles in the powder for layered manufacturing is not particularly limited. The content of the base material particles can be, for example, 60 parts by mass or more, 70 parts by mass or more, 80 parts by mass or more, 85 parts by mass or more, 90 parts by mass or more, and, for example, 99 parts by mass or less, 98 parts by mass or less, or 97 parts by mass or less, based on 100 parts by mass of the total amount of the powder for layered manufacturing.

[0036] The sand as the base particles is not particularly limited so long as it is refractory sand, and examples thereof include one or more types selected from silica sand, olivine sand, zircon sand, chromite sand, alumina sand, and artificial sand.

[0037] The above rapid-setting cement as the base particles can be included as an optional component to further improve early strength development. The above rapid-setting cement is preferably a rapid-setting cement having a (initial) setting time of 30 minutes or less as measured in accordance with JIS R 5210, or a water-stopping cement. Examples of commercially available products such as rapid-setting cement include Super Jet Cement (manufactured by Taiheiyo Cement Corporation), Jet Cement (manufactured by Sumitomo Osaka Cement Co., Ltd.), Lion Shisui (registered trademark, manufactured by Sumitomo Osaka Cement Co., Ltd.), and Denka Super Cement (manufactured by Denka Co., Ltd.). Among them, rapid-setting cement containing gypsum is preferred because the inclusion of a small amount of gypsum improves early strength development.

[0038] The content of the above rapid-hardening cement is preferably 0 to 50 mass%, more preferably 0 to 30 mass%, and even more preferably 5 to 20 mass%, based on 100 mass% of the total solid content of the above molding liquid, in order to improve early strength development and reduce gas generation when used as a mold, etc.

[0039] The above-mentioned cement as the base material particles can be included as an optional component. If the initial setting of the above-mentioned cement is within 3 hours and 30 minutes as measured in accordance with JIS R 5210, it is preferable because the early strength development 3 hours after molding is high, and the initial setting is more preferable within 1 hour. The content of the cement in the above-mentioned molding liquid is preferably 0 to 50 mass%, more preferably 0 to 30 mass%, and even more preferably 0 to 20 mass%, based on the total solid content of the above-mentioned molding liquid as 100 mass%, in order to improve the early strength development.

[0040] The cement may be one or more selected from the group consisting of ordinary Portland cement, high-early-strength Portland cement, moderate-heat Portland cement, low-heat Portland cement, white Portland cement, ecocement, blast-furnace cement, fly ash cement, and cement clinker powder. In the present invention, the cement also includes cement clinker powder.

[0041] The content of calcium silicate in the cement is preferably 25% by mass or more, with the entire cement being 100% by mass. If the content is 25% by mass or more, the strength development after one day of age is high. If long-term strength development is required, the content is preferably 45% by mass or more.

[0042] The adhesive component includes a water-soluble adhesive component and a water-insoluble adhesive component. Examples of the water-soluble adhesive component include a water-soluble adhesive component mainly composed of a thermoplastic resin, a thermosetting resin, a polysaccharide, etc. These may be used alone or in combination of two or more. In this specification, the water-soluble adhesive component refers to resin particles that, when 2 parts by mass of the adhesive component are added to 100 parts by mass of water at a liquid temperature of 90°C and stirred for 4 hours, all or a part of the adhesive component dissolves, and the aqueous solution in which the adhesive component is dissolved exhibits a higher viscosity than water. The water-soluble adhesive component is a component that dissolves in water when mixed with a modeling liquid containing water and bonds base material particles to each other.

[0043] In addition, in this specification, being mainly composed means that the proportion of the above substance in the entire composition (purity of the above substance) is 50% or more by mass, preferably 90% or more, 95% or more, 97% or more, 98% or more, or 99% or more.

[0044] Examples of the thermoplastic resin include vinyl alcohol resin (PVA), isobutylene resin, polyamide resin, and polyester resin.

[0045] The vinyl alcohol resin is a resin containing vinyl alcohol units as a main repeating unit. In the resin, the ratio of the number of moles of vinyl alcohol units to the number of moles of all repeating units is usually 50% or more, and may be 65% or more, 75% or more, or 85% or more. All repeating units may be substantially composed of vinyl alcohol units. The type of repeating unit other than the vinyl alcohol unit in the vinyl alcohol resin is not particularly limited, and may be, for example, vinyl acetate unit.

[0046] Examples of the vinyl alcohol-based resin include anion-modified vinyl alcohol-based resins such as carboxyl group-modified vinyl alcohol-based resins, sulfonic acid group-modified vinyl alcohol-based resins, and phosphate group-modified vinyl alcohol-based resins, cation-modified vinyl alcohol-based resins, and modified vinyl alcohol-based resins copolymerized with ethylene, vinyl ethers having a long-chain alkyl group, vinyl esters, (meth)acrylamide, alpha olefins, and the like.

[0047] The degree of polymerization of the vinyl alcohol resin is not particularly limited, but may be, for example, 100 to 5,000, and preferably 500 to 3,000.

[0048] The isobutylene resin may be a homopolymer of isobutylene, or may be an isobutylene copolymer which is a copolymer of isobutylene and another monomer. In the isobutylene copolymer, the other monomer that is copolymerized with isobutylene is not particularly limited. For example, a monomer having an ethylenic double bond may be mentioned.

[0049] Examples of the monomer having an ethylenic double bond include ethylenically unsaturated carboxylic acids such as maleic acid (anhydride), acrylic acid, methacrylic acid, phthalic acid (anhydride), and itaconic acid (anhydride). Chemically modified isobutylene copolymers may also be used.

[0050] The molecular weight of the isobutylene copolymer is not particularly limited, but may be, for example, 3×10 3 ~2×10 5 , preferably 5 x 10 3 ~1.7×10 5 etc.

[0051] Examples of the polyamide resin include water-soluble nylons obtained by chemically modifying nylons such as polycaproamide (nylon-6).

[0052] The polyester resin may be, for example, a water-soluble polyester in which a component having a hydrophilic group is introduced as a copolymer component into a polyester.

[0053] The thermosetting resin may be, for example, a melamine-based resin.

[0054] Examples of the melamine-based resin include melamine resins obtained by polymerization reaction between melamine and aldehyde, and copolymer resins of a monomer or a prepolymer thereof used to form the melamine resin and another monomer or a prepolymer thereof. In the melamine resin, the aldehyde polymerized with melamine is not particularly limited. Examples of the melamine resin include melamine resins obtained by polymerization reaction between melamine and formaldehyde.

[0055] Examples of the polysaccharides include cellulose derivatives such as hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and carboxymethyl cellulose; and natural polymer compounds such as gum arabic, xanthan gum, curdlan, starch, dextrin, glucomannan, agarose, carrageenan, guar gum, locust bean gum, tragacanth gum, quince seed gum, pullulan, agar, and konjac mannan.

[0056] Other water-soluble adhesive components include, for example, water-soluble adhesive components mainly composed of polyethylene glycol, partially neutralized sodium polyacrylate, polyvinylpyrrolidone, copolymers of polyvinylpyrrolidone, sodium polyacrylate, copolymers of sodium polyacrylate, sodium alginate, sucrose, dextrose, fructose, lactose, gelatin, etc. These may be used alone or in combination of two or more.

[0057] When the water-soluble adhesive component is particulate, the average particle size is not particularly limited, but the average particle size of the water-soluble adhesive component is usually 0.1 μm or more, preferably 1 μm or more. The upper limit of the average particle size of the water-soluble adhesive component is usually 250 μm or less, preferably 200 μm or less.

[0058] The content of the adhesive component in the powder for layered manufacturing is not particularly limited. The content of the adhesive component can be, for example, 1 part by mass or more, 2 parts by mass or more, 3 parts by mass or more, 5 parts by mass or more, 8 parts by mass or more, and, for example, 40 parts by mass or less, 20 parts by mass or less, 10 parts by mass or less, based on 100 parts by mass of the total amount of the powder for layered manufacturing.

[0059] Among the above water-soluble adhesive components, the polyvinyl alcohol-based resin is, for example, a partially saponified or completely saponified product of polyvinyl acetate, and the saponification degree is preferably 85 to 90 mol % because higher early strength development can be obtained.

[0060] In the powder for molding, the mass ratio of the polyvinyl alcohol resin to the base particles is preferably, for example, 0.005 to 0.20. When the ratio is within the above range, the powder is highly de-powderable. The ratio is preferably 0.01 to 0.15, and more preferably 0.015 to 0.10.

[0061] In addition, the average particle size (median diameter, D50) of the polyvinyl alcohol resin is preferably 10 to 150 μm, more preferably 30 to 90 μm, in order to obtain high bending strength. In addition, if the polyvinyl alcohol resin is mixed with an inorganic binder and pulverized to adjust the particle size, the resin becomes finer and can be mixed homogeneously, and the early strength development of the hydraulic composition is further improved.

[0062] Furthermore, the polyvinyl alcohol resin may be used, for example, in a powder state by mixing with the oxide and sand described below, or may be used by dissolving in water described below.

[0063] Furthermore, the above-mentioned shaped object preferably contains the oxide in an amount of, for example, 50 parts by mass or more per 100 parts by mass of the entire shaped object, and may also contain 60 parts by mass or more, 70 parts by mass or more, 80 parts by mass or more, 85 parts by mass or more, or 90 parts by mass or more.

[0064] In addition, in the above-mentioned modeling powder, known additives that can be used in powders for three-dimensional modeling, such as inorganic powders other than the above-mentioned oxides, dispersants, thickeners, printing aids, etc., can be used within a range that does not impair the effects of the present invention.

[0065] The inorganic powder other than the oxide is, for example, a nitride, a carbide, a sulfide, etc., and SiC, Si 3 N 4 , AlN, and the like.

[0066] The shape of the inorganic powder other than the oxide may be, for example, spherical, elliptical, non-spherical, etc. The average particle size (median diameter, D50) of the inorganic powder is not particularly limited, but may be, for example, 1 μm or more and 200 μm or less. From the viewpoint of moldability, the average particle size of the inorganic powder may be, for example, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. In addition, the average particle size of the inorganic powder may be, for example, 200 μm or less, and 140 μm, 120 μm, 100 μm, 80 μm, or 60 μm or less.

[0067] The preparation method of the powder for molding is not particularly limited. For example, the components contained in the powder for molding can be mixed using a well-known mixing method such as premixing. The manner in which the components are mixed is not particularly limited, and for example, all the components may be mixed at once, or may be mixed in an appropriately set order.

[0068] The above-mentioned molding powder is typically mixed with a molding liquid containing water and used for molding a model.

[0069] The solvent used in the modeling liquid is preferably a solvent containing water. Examples of the solvent include pure water, ultrapure water, ion-exchanged water (deionized water), and distilled water. The modeling liquid may further contain an organic solvent that can be mixed uniformly with water, such as a lower alcohol or a lower ketone, as necessary. Usually, it is preferable that 40% by volume or more of the solvent contained in the modeling liquid is water, and more preferably 50% by volume or more, typically 50 to 100% by volume, is water. Such a modeling liquid can be mixed at a ratio of, for example, 20 to 80 parts by mass, typically 40 to 60 parts by mass, per 100 parts by mass of the powder for three-dimensional solid modeling during modeling.

[0070] The above-mentioned modeling liquid may further contain, as necessary, known additives that can be used in modeling liquids, such as dyes, organic pigments, inorganic pigments, wetting agents, flow rate enhancers, etc., within a range that does not impair the effects of the present invention. The content of the above-mentioned additives may be appropriately set depending on the purpose of adding them.

[0071] The method of forming a model using the modeling powder is not particularly limited. For example, a layer of powder is formed using the modeling powder, and then a modeling liquid containing water is supplied to a predetermined area of ​​the layer to form a model. This modeling can be performed, for example, using a 3D printer that forms a solid object based on three-dimensional data corresponding to the model to be formed. The 3D printer can have, for example, an inkjet that drops a modeling liquid containing water, and a table on which the modeling powder is placed.

[0072] In the above-mentioned shaping method, for example, the following steps 1 to 3 are repeated to sequentially stack layered solids to form a shaped object. Step 1: The above-mentioned modeling powder is layered on a mounting table to a thickness corresponding to each layer of the model to be formed, for example, 0.01 mm to 0.5 mm. Step 2: A modeling liquid containing water is dropped from an inkjet head onto the part of the layered modeling powder (sediment) that should be hardened. The water-soluble adhesive component contained in the dropped part dissolves and bonds the base material particles together, forming a layered solid. Operation 3: The table is lowered vertically downward by the thickness corresponding to each layer of the layered solid material.

[0073] After the above operation, the uncured powder for modeling is finally removed to complete the modeling of the model. The model is formed by bonding a large number of base material particles with the dissolved water-soluble adhesive component, and may have a porous structure. After modeling, the obtained model may be naturally dried. The drying time is not particularly limited, but is, for example, about 1.5 hours to 24 hours, preferably 15 hours to 20 hours.

[0074] The additive manufacturing equipment used to form the above-mentioned shaped body is not particularly limited, but examples include binder injection type powder lamination molding equipment such as the ProJet 660Pro manufactured by 3D Systems, the S-Max manufactured by ExOne, the VX4000 manufactured by Voxeljet, and the SCM-1800 manufactured by Seemet.

[0075] <Methods for improving the strength of objects> The method for improving strength of a shaped object of the present invention comprises the steps of: A step (1) of impregnating a shaped object containing an oxide containing at least one element selected from the group consisting of Si, Al, Ca, Zr, Ti, Fe, Cr, and Mg with at least one silica-containing liquid containing a silica sol solution or an alkyl silicate solution; A step (2) of subjecting the object processed in the step (1) to a heat treatment at 800°C or higher; A step (3) of impregnating the shaped object treated in the step (2) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and The method includes a step (4) of subjecting the shaped object treated in the step (3) to a heat treatment at 800° C. or higher, At least one of the above step (2) or the above step (4) is a heat treatment at 1000° C. or higher.

[0076] The above-mentioned step (1) is a step of impregnating the above-mentioned shaped object with at least one kind of silica sol solution or a silica-containing liquid containing an alkyl silicate solution (hereinafter, also referred to as "impregnation step (1)").

[0077] The silica-containing liquid is at least one selected from a silica sol solution, which is a colloidal solution in which ultrafine particles of silicic anhydride at nano level are dispersed, and a non-monomer alkyl silicate solution. Of these, the dispersion medium of the silica sol solution is water or a water-soluble organic solvent, and the dispersion medium of the alkyl silicate solution is a water-soluble organic solvent. Among the dispersion solvents, organic solvents are preferred because they do not react with the shaped object and cause little dimensional change in the shaped object.

[0078] The alkyl group of the alkyl silicate is easily available, and examples thereof include a methyl group, an ethyl group, an isopropyl group, etc. These may be used alone or in combination of two or more kinds.

[0079] The alkyl silicate in the alkyl silicate solution is preferably a dimer or higher alkyl silicate. The reason why monomeric alkyl silicate is excluded from the alkyl silicate solution is that the bending strength of a shaped object permeated with the monomeric alkyl silicate solution is low, and the surface can be scratched with fingers. Furthermore, from the viewpoint of increasing the strength of the shaped object, the alkyl silicate in the alkyl silicate solution is preferably a pentamer or higher alkyl silicate.

[0080] The viscosity of the silica-containing liquid at 25° C. is preferably 50 mPa·s or less, more preferably 40 mPa·s, and even more preferably 30 mPa·s, in order to enhance the permeability into the shaped object.

[0081] The impregnation step (1) is not particularly limited, and may be, for example, spraying or applying a silica-containing liquid to the shaped object, or immersing the shaped object in the silica-containing liquid. The penetration depth of the silica-containing liquid is preferably 0.4 to 10.0 mm. If the penetration depth is less than 0.4 mm, the bending strength of the shaped object is low and the surface condition is poor, and if it exceeds 10.0 mm, it takes a long time to penetrate, so that the manufacturing efficiency decreases. The penetration depth of the silica-containing liquid is more preferably 0.5 to 6 mm. The penetration depth was determined by cutting the shaped object after the impregnation treatment (and further after the heat treatment) with a diamond cutter and measuring the silica impregnated area on the cross section. The impregnated area was determined by the naked eye, a microscope, an optical microscope, and a scanning electron microscope.

[0082] The permeation time of the silica-containing liquid is preferably 5 to 120 seconds. If the permeation time is less than 5 seconds, the permeation is insufficient, and if it exceeds 120 seconds, the permeation tends to be saturated. The immersion time of the silica-containing liquid is more preferably 10 to 100 seconds. After the shaped product is permeated with the silica-containing solution, it is preferable to leave it for 6 hours to 2 days to promote the diffusion of the silica-containing solution in the molded product.

[0083] The step (2) is a step of subjecting the shaped object treated in the step (1) to a heat treatment at 800° C. or higher (hereinafter, also referred to as “heating step (2)”).

[0084] The heating step (2) is not particularly limited because it depends on the size of the object, and examples of the heating method include a heating method in which the object is heated to 800 to 2000°C in an electric furnace over 2 to 10 hours, the temperature is maintained for 30 minutes to 2 hours, and then cooled to room temperature over another 2 to 10 hours. When the object is heated to 500°C or higher, most of the bound water of the mineral and polyvinyl alcohol resulting from the hydration reaction of the cement volatilizes, and the volatile content decreases as the object is heated to a higher temperature. On the other hand, the object may melt when heated to a temperature exceeding 2000°C. The heating temperature of the object may be 850 to 1800°C, 900 to 1600°C, 950 to 1400°C, or 1000 to 1200°C.

[0085] The heating step (2) is generally performed using an electric furnace or a combustion furnace, but is not limited to these. For example, in casting, a phenomenon occurs in which the molded object is heated by contact with the molten metal.

[0086] The above-mentioned step (3) is a step of impregnating the shaped object treated in the above-mentioned step (2) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution (hereinafter, also referred to as "impregnation step (3)").

[0087] The above impregnation step (3) can be appropriately carried out in the same manner as the impregnation step (1).

[0088] The step (4) is a step of subjecting the shaped object treated in the step (3) to a heat treatment at 800° C. or higher (hereinafter, also referred to as “heating step (4)”).

[0089] The heating step (4) can be carried out in the same manner as the heating step (2) as appropriate.

[0090] However, at least one of the above step (2) or the above step (4) is a heat treatment at 1000° C. or higher. By having the above configuration, for example, the bending strength can be made to be 10 MPa or higher.

[0091] In addition to the above steps (1) to (4), the method may further include a step of impregnating the shaped object treated in the above step (4) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution (hereinafter also referred to as "impregnation step (5) etc."), and a step of heating the shaped object treated in the above step (5) at 800°C or higher (hereinafter also referred to as "heating step (6) etc."). (Furthermore, impregnation step (7) and heating step (8), impregnation step (9) and heating step (10), impregnation step (11) and heating step (12), etc.) The impregnation step (5) etc. and heating step (6) etc. may be appropriately performed in the same manner as the above steps (1) to (4).

[0092] In addition to the above steps (1) to (4) (including the impregnation step (5) and the heating step (6)), a heating step at less than 800°C and a drying step may be appropriately included before or after each step.

[0093] <Method of manufacturing reinforced objects> The method for producing a reinforced shaped object of the present invention comprises the steps of: A step (1) of impregnating a shaped object containing an oxide containing at least one element selected from the group consisting of Si, Al, Ca, Zr, Ti, Fe, Cr, and Mg with at least one silica-containing liquid containing a silica sol solution or an alkyl silicate solution; A step (2) of subjecting the object processed in the step (1) to a heat treatment at 800°C or higher; A step (3) of impregnating the shaped object treated in the step (2) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and The method includes a step (4) of subjecting the shaped object treated in the step (3) to a heat treatment at 800° C. or higher, At least one of the above step (2) or the above step (4) is a heat treatment at 1000° C. or higher.

[0094] The reinforced shaped article in the production method of the present invention refers to an article whose strength has been improved by a method including the above steps (1) to (4).

[0095] The above steps (1) to (4) can be appropriately carried out in the same manner as the above steps (1) to (4) in the above-mentioned strength improvement method (which may further include an impregnation step (5) and a heating step (6), etc.). EXAMPLES

[0096] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0097] [Examples 1 to 7, Comparative Examples 1 to 10] A binder injection powder lamination molding machine (product name: ProJet160Pro, manufactured by 3D Systems) was used as an additive manufacturing device to create test pieces (molded bodies) with cross-sectional dimensions of 16 mm length, 10 mm width, and 80 mm length. After each treatment, the test pieces were used for each measurement and evaluation. The materials used are shown in Table 1. The water volume setting value from the nozzle of the device was 88% for the inside (core) of the molded body and 122% for the outside (shell).

[0098] [Table 1]

[0099] (Powder A) As the powder A in Table 1 above, a hydraulic composition for additive manufacturing devices was used, which was obtained by mixing the following (1) calcium aluminate, (2) Espearl, (3) Cerabeads, and (4) crushed Cerabeads in a weight ratio of 0.3:1:1:0.7 to obtain 100 mass% mixture, and adding 2 mass% of (5) polyvinyl alcohol.

[0100] (1) Calcium aluminate As a prototype of amorphous calcium aluminate, CaO / Al 2 O 3 The molar ratio is 2.2, the vitrification rate is 95% or more, and the Blaine specific surface area is 2710 cm 2 The diameter of the pores was 1 / g. The D50 was 24 μm.

[0101] (2) Espar Espearl #180L (manufactured by Yamakawa Sangyo Co., Ltd., alumina-based spherical low-expansion aggregate) was used. The chemical composition is shown in the table below. D50 was 75 μm.

[0102] [Table 2]

[0103] (3) Cerabeads Naigai Cera Beads #1450 (manufactured by Itochu Ceratec Co., Ltd., artificial ceramic sand made of mullite crystals) was used. The chemical composition is shown in the table below.

[0104] [Table 3]

[0105] (4) Crushed Cerabeads The NAIGAI CERA BEAD was ground in a ball mill to obtain a powder, and the D50 was 30 μm.

[0106] (5) Polyvinyl alcohol Part number 22-88 S1 (PVA217SS, manufactured by Kuraray Co., Ltd.) was used. The degree of saponification was 87 to 89%, the average particle size (D50) was 60 μm, the content of particles larger than 94 μm was 29%, and the content of particles larger than 77 μm was 47 mass%, the 10% diameter (D10) was 25 μm, and the 90% diameter (D90) was 121 μm.

[0107] (Silica liquid B) Silica sol dispersed in isopropyl alcohol (IPA-ST, manufactured by Nissan Chemical Industries, Ltd.) was used as the silica liquid B in Table 1. The chemical composition and the like are shown below. ·Solid content wt%: 30wt% ·Particle size: 10~15nm Viscosity at 25°C: 1.0 to 20.0 mPa s ·Moisture: 2% or less

[0108] The obtained molded bodies were subjected to tests under the various conditions shown in Table 4.

[0109] [Table 4]

[0110] <Processing conditions in Examples and Comparative Examples> Example 1: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 1100°C Example 2: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C Example 3: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C Example 4: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C Example 5: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 1100°C Example 6: Impregnation treatment → Heat treatment at 800°C → Impregnation treatment → Heat treatment at 1100°C Example 7: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 800°C Comparative Example 1: Impregnation treatment → Heat treatment 100℃ Comparative Example 2: Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 100°C Comparative Example 3: Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 1100°C Comparative Example 4: Impregnation treatment → Heat treatment 1100℃ Comparative Example 5: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 100°C Comparative Example 6: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 100°C Comparative Example 7: Impregnation treatment → Heat treatment at 1100°C → Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 100°C → Impregnation treatment → Heat treatment at 100°C Comparative Example 8: Impregnation treatment → Heat treatment at 800℃ Comparative Example 9: Impregnation treatment → Heat treatment 1500℃ Comparative Example 10: Untreated molded body

[0111] *Details of each process The impregnation treatment was carried out by placing the molded body in a container filled with silica-containing liquid so that the entire body was immersed, leaving it to stand for 60 seconds, and then removing the molded body from the silica-containing liquid and drying it for 24 hours. For example, in the case of a 100°C heat treatment, the molded body was placed in a dryer (Tokyo Rika Kikai Co., Ltd., model number: LTI-600SD) set to 100°C and left to stand for 24 hours, after which the dryer was turned off and the body was gradually cooled to room temperature. In the case of heating at a heating temperature of 800°C or higher, the body was gradually heated to the top temperature using a cart-lifting high-temperature atmospheric furnace (Nemus Co., Ltd., model number: WUD70×70×70-2Z2-12), held at each top temperature for 1 hour, and then slowly cooled to room temperature. The heating and cooling rates were both set to 200°C / 1h. Impregnation treatment: Impregnation treatment in silica liquid B for 60 seconds Heat treatment at 100℃: Heat treatment at 100℃ for 24 hours Heat treatment at 800℃: Heat treatment at 800℃ for 1 hour Heat treatment at 1100℃: Heat treatment at 1100℃ for 1 hour Heat treatment at 1500℃: Heat treatment at 1500℃ for 1 hour

[0112] The results of the bending strength are shown in Table 5 and Figures 1 to 3. Table 5 also shows the results of the dimensional change and the mass loss.

[0113] [Table 5]

[0114] <Measurement and evaluation conditions> (Bending strength measurement, dimensional change measurement) Using the molded bodies that had undergone each treatment, a three-point bending test was carried out using a bending strength tester (model number: MODEL-2257, manufactured by Aiko Engineering Co., Ltd.) to measure the bending strength and dimensions of each of the treated molded bodies.

[0115] (Measurement of mass loss rate) The mass loss rate of each treated molded body was measured using a thermal analyzer (Bruker A.X., model number: TG-DTA2000SR). The temperature was raised from room temperature to 1000°C at 20°C / min, and the mass loss rate was calculated from the change in mass of the sample at room temperature and 1000°C.

[0116] <Judgment criteria> In the measurements of bending strength, dimensional change, and mass reduction rate, the desired reinforced objects were those that satisfied the following criteria. Bending strength standard: 10MPa or more Dimensional standard: ±2% or less Mass reduction rate standard: 0.5 or less (related to the amount of gas generated; too much will cause defects in castings, etc.)

[0117] As shown in Table 5 and Figures 1 to 3, the results of each evaluation showed that when the molded bodies of Examples 1 to 7 were used, the above-mentioned desirable strength improvement effects were observed in the bending strength measurement, dimensional change measurement, and mass loss rate measurement.

Claims

1. A process (1) of impregnating a shaped object containing an oxide containing Ca with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; A step (2) of subjecting the shaped object treated in the step (1) to a heat treatment at 800° C. or higher; A step (3) of impregnating the shaped object treated in the step (2) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and A step (4) of subjecting the shaped object treated in the step (3) to a heat treatment at 800° C. or higher, At least one of the steps (2) and (4) is a heat treatment at 1000° C. or higher; The method for improving strength of a shaped object, wherein the alkyl silicate in the alkyl silicate solution is an alkyl silicate having a dimer or higher.

2. The method for improving strength of a structure according to claim 1 , wherein the structure is manufactured by an additive manufacturing device.

3. The strength improving method according to claim 1 or 2, wherein the shaped object contains the oxide in an amount of 50 mass % or more based on the entire shaped object.

4. The strength improving method according to any one of claims 1 to 3, wherein the impregnation treatment in the step (1) is carried out for 5 to 120 seconds.

5. The strength improving method according to any one of claims 1 to 4, wherein the alkyl silicate in the alkyl silicate solution is an alkyl silicate having a polymer content of five or more.

6. A strength improvement method described in any one of claims 1 to 5, wherein the structure further contains at least one element selected from the group consisting of Si, Al, Zr, Ti, Fe, Cr, and Mg.

7. The strength improving method according to any one of claims 1 to 6, wherein the heat treatment in the step (2) is performed at 2000°C or less.

8. The strength improving method according to any one of claims 1 to 7, wherein the heat treatment in the step (4) is performed at 2000°C or less.

9. moreover, A step (5) of impregnating the shaped object treated in the step (4) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and The strength improving method according to any one of claims 1 to 8, further comprising a step (6) of subjecting the shaped object treated in the step (5) to a heat treatment at 800°C or higher.

10. The strength improving method according to claim 9, wherein the heat treatment in the step (6) is performed at 2000° C. or less.

11. The strength improving method according to any one of claims 1 to 10, wherein the shaped article is used for a casting mold.

12. A process (1) of impregnating a shaped object containing an oxide containing Ca with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; A step (2) of subjecting the shaped object treated in the step (1) to a heat treatment at 800° C. or higher; A step (3) of impregnating the shaped object treated in the step (2) with at least one type of silica sol solution or a silica-containing liquid containing an alkyl silicate solution; and A step (4) of subjecting the shaped object treated in the step (3) to a heat treatment at 800° C. or higher, At least one of the steps (2) and (4) is a heat treatment at 1000° C. or higher; A method for producing a reinforced shaped article, wherein the alkyl silicate in the alkyl silicate solution is an alkyl silicate having a dimer or higher.

13. The method for manufacturing a reinforced shaped object described in Claim 12, wherein the shaped object further contains at least one element selected from the group consisting of Si, Al, Zr, Ti, Fe, Cr, and Mg.

Citation Information

Patent Citations

  • Production of fiber reinforced ceramics

    JP1988288974A

  • Porous ceramic formed body and its manufacturing method

    JP2006327913A

  • High heat-resistance powder for forming inkjet powder lamination mold

    JP2011051010A

  • Ceramic casting core made by additive manufacturing

    JP2015226935A

  • Manufacturing method of mold

    JP2016159324A